Electromyographic Comparison of a Stability Ball Crunch With a Traditional Crunch - Sternlicht, Eric; Rugg, Stuart; Fujii, Larissa L.; Tomomitsu, Keri F.; Seki, Matt M. (Journal of strength and conditioning research, 2007)
The purpose of this study was to compare abdominal muscle activity while performing a crunch on a stability ball with a traditional crunch. Forty-one healthy adults (23 men and 18 women) participated in the study. The subjects performed the crunch with the ball in 2 positions, 1 with the ball at the level of the inferior angles of the scapula (SB-high) and 1 with the ball at the level of the lower lumbar region of the back (SB-low). Surface electromyography was recorded from the upper and lower portions of the rectus abdominis and the external oblique during each repetition. Electromyography values were analyzed using repeated measures analyses of variance and pair-wise comparisons. Muscle activity for the upper and lower portions of the rectus abdominis and external oblique for a traditional crunch was significantly lower than for the crunch performed in the SB-low position but significantly greater than the SB-high position. Our data also showed that, on average, the abdominal muscle activity doubled when the stability ball was moved from the upper to the lower back position. These results support previous findings that a stability ball is not only effective for training the abdominal musculature, but, with the correct placement, it can also significantly increase muscle activity when compared with a traditional crunch. In addition, our results suggest that ball placement is critical for matching the appropriate overload to the condition level of the user. [PUBLICATION ABSTRACT]